Autonomia e vinculação dos órgãos e entidades da Administração Pública no exercício de atividade sancionatória e a aplicabilidade do princípio do non bis in idem - Henriques, Diana Carolina Biseo (2019)
The present study aims to analyse the limits of the sanctioning activity of the Public Administration, considering the contemporary settling of the administrative organization, and its polycentric character, what implies revisiting old dogmas of Administrative Law, like the concept of its hierarchical internal relations. In a scenario where administrative bodies and entities are entitled to some autonomy, they can share the competence to apply sanctions related to a given subject, which could generate a punitive overflow towards the individual. This punitive overload is not aligned with the current Brazilian legal system, especially with the protective aspect of the sanctioning Administrative Law that, even oriented to reprehend the offending agent whose behaviour is not supported by the legal system, in the other hand is intended to safeguard the material and procedural guarantees of the accused, including the implications deriving from the non bis in idem principle. The interpretation of the sanctioning Administrative Law must consider this principle in both material and procedural perspectives, claiming the reformulation of inter-organic relations into the Public Administration structure